Factors associated with receiving an HIV test among patients admitted through the emergency unit at a Kenyan referral hospital. (January 2018) - Bridge, Rebecca; Lin, Janet
Despite decreasing incidence, HIV is the leading cause of morbidity and mortality in Kenya. In Kisumu, HIV prevalence is ∼19% and incidence is second highest in the country. There is a need to identify HIV-positive persons and link them to care. Universal testing in healthcare facilities is a strategy supported by the Kenyan government to facilitate identification of new HIV cases. The objective was to identify patterns of HIV testing in a hospital in Kisumu, Kenya, a setting where universal testing is recommended. A retrospective chart review of patients seen between January 2014 and December 2014 was conducted. We collected information on 5% of admitted patients older than 18 years of age. Chi square analysis characterized patients and Poisson regression modeling produced the relative risk of being tested. In 2014, 9071 patients were admitted from the emergency unit. From the sample, 24% of patients were recorded to have been tested for HIV. There was no significant difference in testing between genders (p = 0.99). Females with a genitourinary diagnosis were significantly more likely to be tested for HIV than other diagnoses (adjusted relative risk [aRR] = 1.79). Males with an infectious disease were 1.86 times more likely to be tested for HIV than other diagnoses, while females with pregnancy-related diagnoses were 50% less likely to be tested for HIV (aRR = 0.50). While universal testing supports a non-risk-based screening of patients, higher risk diagnoses were more likely to be tested. This study demonstrates that there is still opportunity to further practice and implement universal testing.